Comprehensive analysis of prognostic factors and clinical implications of pneumonectomy for destroyed lung - Shanbo Zheng; Akbar Anwar; Wancheng Zhong; Xiaogang Yan (Frontiers in Surgery, 2026)
Background Evaluate the efficacy and safety of pneumonectomy in the treatment of destroyed lung caused by benign diseases, and identify the risk factors for postoperative complications. Methods We retrospectively analyzed 158 patients with destroyed lung caused by benign diseases who underwent pneumonectomy in a single center from January 2014 to December 2024. Cases were assigned to tuberculosis (TB) group and non-tuberculosis (non-TB) group. Clinical characteristics and postoperative complications were analyzed and compared between groups. Univariate and multivariate analyses were performed to investigate the risk factors of pneumonectomy. Results A total of 125 TB and 33 non-TB patients were included. All patients with preoperative hemoptysis recovered after surgery. Major postoperative complications were observed in 32 patients (20.3%), and perioperative deaths were noted in three patients (1.9%), who were from the TB group. The TB group had a longer duration of surgery and length of stay in the intensive care unit (ICU), a higher proportion of diabetes and postoperative complications (24.0% vs. 6.1%, p = 0.027) than the non-TB group. Multivariate logistic analyses indicated diabetes [odds ratio [OR]: 4.680; 95% conﬁdence interval [CI]: 1.578–13.881; p = 0.005] and duration of surgery (OR: 1.005; 95% CI: 1.001–1.010; p = 0.036) were the independent risk factors of postoperative complications of pneumonectomy. Conclusion Pneumonectomy is effective for destroyed lung caused by benign diseases. Patients with TB destroyed lung have a higher risk of postoperative complications. Controlling perioperative blood glucose and reducing duration of surgery may reduce the risk of perioperative complications.